Sustainable governance and technological innovation: Moderating environmental risks of resource rents - Shao, Xuefeng (2026)
Over the years, the over-extraction and unsustainable utilization of natural resources has started to pose a severe environmental risk, necessitating immediate action on issues related to climate change. Therefore, this study examines the relationship between natural resources rent and environmental risk, and whether financial technology (FinTech) and institutional quality moderate this relationship in the context of the top 27 contaminating countries from the years pertaining to 1995 to 2022. Using the novel Method of Moments Quantile Regression (MMQR) approach, our study analyzes heterogeneous long-run coefficients across 10th, 25th, 50th, 75th, and 90th quantiles of environmental risk. In this regard, the MMQR findings have revealed that natural resources rent leads to an increase in the environmental risk, while FinTech and institutional quality tend to mitigate it. The moderation effect models revealed that both FinTech and institutional quality suppress the adverse environmental outcomes that are exerted by the natural resources rent. The Driscoll and Kray standard error (DKse) and Fully Modified Ordinary Least Square (FMOLS) estimation techniques confirm the robustness of the MMQR findings. These findings emphasize that policymakers and think tank initiatives should promote FinTech and robust institutions to encourage sustainable resource utilization in order to mitigate the environmental crisis.